TRANSFORMASI PERAN PESANTREN DALAM PENGEMBANGAN MANAJEMEN BISNIS SYARIAH DI LINGKUNGAN PENDIDIKAN KABUPATEN BREBES - Abdau, Faizal; Pramono, Setya (An Nuqud Journal of Islamic Economics, 2025)
This study aims to explore the role of Pondok Pesantren Imam Syafi'i in improving business literacy among santri in Brebes Regency. Business literacy, as the ability to understand and apply business concepts, is an important element in equipping santri with practical skills relevant to the needs of modern society. Using a qualitative approach through a case study, this research identifies strategies implemented by pesantren, such as business curriculum integration, entrepreneurship training, and independent business management programs. The results show that the business literacy program in this pesantren has a positive impact on improving santri's understanding and business skills, which in turn can increase their economic independence. However, there are challenges such as limited resources and external support. This research is expected to be a reference for the development of similar programs in other pesantren in Indonesia